Ensuring sustainable agriculture by analyzing the European Union and Romanian legislation on soil resources protection - Bogdan Vasile Cioruța; Mirela Ana Coman (International Journal on Food, Agriculture and Natural Resources, 2022)
Soil is considered to be one of the most complex natural systems on the planet, a key component of the geographical environment, and a biological complex that is constantly changing. Also, the soil is a multifunctional system on which the essential functions of life on Earth are based. As such, soil protection must be a primary concern for the community, as the conservation of soil resources itself requires more than transposition in legislative terms. Thus, on the protection of soils from the point of view of the legislation of the EU and Romania, we set out to make an analysis noting in this paper the main provisions of the acquis communautaire (directives, strategies, decisions, etc.), which come to ensure an interface between the use of soils and their protection for future generations. As a result of the research undertaken we can conclude that both EU and Romanian legislation are still deficient in soil protection, it is not as protected as the other elements of the environment, water, air, and/or biodiversity.